Discours grammaticaux et linguistiques: de la transposition à la transposabilité en didactique du FLE - Sofiane Assiakh; Sadi Nabil (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2017)
This article proposes to rethink the possibility of exploiting the contributions of fundamental linguistics for didactic purposes, in particular, teaching grammar of the French as a foreign language (FFL). Comparing the linguistic scientificity / didacticity of grammatical and linguistic discourses as to the description of the prepositions of the French language allowed us to highlight the gaps characterizing grammars in their description of the grammatical facts. We shall focus first on the linguistic scientificity and the didacticity of three most frequently used grammars in the teaching / learning of the grammar of FFL in Algeria. In a second step, we will try to do the same with three linguistic theories in order to highlight the possibility of developing a thinking on a scientific and a didactic grammar in class of language.